A compact tri‐band microwave resonator for ethanol gas detection. Issue 10 (10th July 2019) - Mohammed, Gulam Nabi Alsath; Savarimuthu, Kirubaveni; Erattaiselvam, Velkani; Rapuru, Srinithya; Yarasi, Tusharika; Dommalapati, Navya
Abstract: This article presents the design, simulation, fabrication, and testing of a compact two‐port microwave resonator coated with nanomaterials for ethanol gas sensing applications. The proposed gas sensor consists of a transmission line loaded with three triangular split ring resonators for ethanol detection at three frequency bands viz. 2.2, 4.6, and 6.3 GHz. The transmission line has all‐pass characteristics in which band gaps are introduced using three split ring resonators. The TiO2 and ZnO nanorods are used as sensitive layers for the proposed sensing application. The nanorods, which are grown on a glass substrate of thickness 1 mm, are loaded on to the two‐port microwave resonator making the device sensitive to ethanol. The microwave behavior of the sensor is analyzed using the scattering parameters. The absorption of the ethanol gas causes frequency detuning which is used to analyze the presence of ethanol and its concentration. From the experiments, it is understood that there is an increase in the frequency shift with an increase in the concentration of ethanol gas. The sensing device with ZnO as a sensitive layer showed a higher average sensitivity of 2.35 compared to TiO2 whose average sensitivity is 1.29.